Educational Institutions Still Eager to Establish a Branch Campus in Dubai - Wilkins, Stephen (International Higher Education, 2024)
The Emirate of Dubai has a population of only 3.65 million but more than 70 higher education institutions, making its higher education market fiercely competitive. However, each year foreign institutions continue to arrive, eager to establish a new campus in the emirate. This article discusses the motivations of these institutions for establishing a campus in Dubai, the strategies that they intend to implement, and the impacts of these new arrivals on Dubai’s higher education market.